Analysis of Game Variables and Influence on Defensive Success in Elite Handball - González-García, Iván (Physical Education and Sports: Studies and Research, 2024)
Background: The analysis of defensive game variables in handball is essential to increase the performance of a team. Objectives: This study aimed to analyse defensive success based on the game variables and situational variables that predict defensive efficiency in elite handball. Methods: The sample was composed of 1925 competition units in the defensive phase. Data from 16 matches of the XXIII Men's Handball World Championship of 2013 were analysed. The dependent variable was the defensive efficiency in each unit, and the independent variables were defensive actions, zones of field, location of the shot, numerical situation, and duration of the defense. Data were obtained from the HandballTAS tool (Handball Tactic Analysis System). The collected data were analysed quantitatively through inferential statistics (independent sample t-test) with the assistance of SPSS 22.0. Results: The defenses analysed in which an offensive foul, a ball recovery or steal, a throw block and a passive play action were recorded, achieved defensive success. In the analysis of field areas, the greatest defensive efficiency was obtained in shots from zone 1, with 60%, and from zone 2, with 54%. The highest percentages of goalkeeper effectiveness correspond to the middle zone, and the central zone. The greatest defensive efficiency was obtained in a warning of passive play situation with 70% and in numerical superiority situation with 67%. Finally, in the analysis of the duration, the greatest defensive efficiency was obtained in the half defenses (26 ≤ 50 seconds) with 60%. Conclusion: This study serves to demonstrate which defensive game variables have the greatest influence on defensive efficiency. This aspect will serve to help the coach make decisions during a handball match and increase the probability of success in each defense.